Respuestas
Respuesta dada por:
3
Hola! ^º,.,º^
![3( {x}^{3} - 1) = - 27 \\ \\ {x}^{3} - 1 = - 9 \\ \\ {x}^{3} = - 9 + 1 \\ \\ { x }^{3} = - 8 \\ \\ x = \sqrt[3]{ - 8} \\ \\ x = - 2 3( {x}^{3} - 1) = - 27 \\ \\ {x}^{3} - 1 = - 9 \\ \\ {x}^{3} = - 9 + 1 \\ \\ { x }^{3} = - 8 \\ \\ x = \sqrt[3]{ - 8} \\ \\ x = - 2](https://tex.z-dn.net/?f=3%28+%7Bx%7D%5E%7B3%7D++-+1%29+%3D++-+27+%5C%5C++%5C%5C++%7Bx%7D%5E%7B3%7D++-+1+%3D++-+9+%5C%5C++%5C%5C++%7Bx%7D%5E%7B3%7D++%3D++-+9+%2B+1+%5C%5C++%5C%5C+%7B+x+%7D%5E%7B3%7D++%3D++-+8+%5C%5C++%5C%5C+x+%3D++%5Csqrt%5B3%5D%7B+-+8%7D++%5C%5C++%5C%5C+x+%3D++-+2)
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años